Effects of Nanoparticles on Double-Stranded RNA Stability in Corn Soil - Reyanldo, Miriam; Cooper, Anastasia; Song, Huifang; Yu, Zhitao; Zhang, Hao; Silver, Kristopher; Zhang, Jianzhen; Zhu, Kun Yan (My University, 2018)
Double-stranded RNA (dsRNA) can potentially be used as a pesticide because these molecules trigger an immune response called RNA interference (RNAi). If the expression of essential genes matching the dsRNA sequence are silenced, then the pest dies. New classes of pesticides, including RNAi-based pesticides, are needed to overcome pesticide resistance and reduce the environmental impacts of pesticides. Unfortunately, dsRNA is easily degraded by enzymes in the environment, particularly those produced by microbes in the soil (Dubelmanet al., 2014),severely limiting delivery of dsRNA to cryptic (soil dwelling) species unless transgenic plants are used. Here we investigate dsRNA stability when incubated in corn soil supernatant ex situ to determine if encapsulation of dsRNA in chitosan-basednanoparticles (CB-NPs) enhances stability in corn soil. Interestingly, dsRNA stability was not affected by soil supernatant, possibly due to the time of year when sampling was performed (Icozet al., 2008). Nonetheless, these findings provide insight into dsRNA stability in soil, and in the future may lead to a method for protecting dsRNA from environmental degradation using CB-NPs.
Keywords: Fall 2018